(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Some factors that can influence a performance are motivation and work discipline. Therefore this research aims to determine and analyze the influence of motivation towards employee performance with work discipline as a mediating variable at PT. Pos Indonesia (Persero) Denpasar City. Sampling using the saturated sample method, amounting to 93 people. Data collection by distributing questionnaires. The data analysis technique is the path analysis technique using the SPSS version 21 program. The results of the analysis show that (1) work motivation has a positive and significant (real) influence towards work discipline, (2) work motivation has a positive and significant (real) influence towards employee performance, (3) work discipline has a positive and significant (real) influence towards employee performance, (4) work discipline has a positive and significant role in mediating the work motivation on improving employee performance. The advice given is to pay attention to employee relations with other employees so there will not be any conflicts occur. Acting decisively on employees whose absences exceed the tolerance limits of the company and increase employee motivation also increasing work discipline.